Protective effect of sensory denervation in inflammatory arthritis (evidence of regulatory neuroimmune pathways in the arthritic joint). Issue 2 (21st May 2004) - Kane, D; Lockhart, J C; Balint, P V; Mann, C; Ferrell, W R; McInnes, I B
Abstract : Objective: To investigate the direct effect of joint innervation on immune mediated joint inflammation in a patient with psoriatic arthritis (PsA). Case report: The patient developed arthritis mutilans in all digits of both hands with the exception of the left 4th finger, which had prior sensory denervation following traumatic nerve dissection. Plain radiography, ultrasonography and nerve conduction studies of the hands confirmed the absence of articular disease and sensory innervation in the left 4th digit. Methods: This relationship between joint innervation and joint inflammation was investigated experimentally by prior surgical sensory denervation of the medial aspect of the knee in six Wistar rats in which carrageenan induced arthritis was subsequently induced. Prior sensory denervation—with preservation of muscle function—prevented the development of inflammatory arthritis in the denervated knee. Discussion: Observations in human and animal inflammatory arthritis suggest that regulatory neuroimmune pathways in the joint are an important mechanism that modulates the clinical expression of inflammatory arthritis.